The unintended consequences of good intentions - Debra Tavaras (Adult Education Research Conference, 2021)
Adult education programs encourage adults to attend college after they receive their GED, yet the programs do not prepare them for the transition or on how to be successful. Colleges and adult education programs do not give enough attention to the challenges and barriers the adult learner faces. Programs assume that adult learners know how to balance the rigour of college and their other responsibilities. After all they are adults. Yet, studies have shown that 77% of GED graduates who attend community and technical colleges withdrew at the end of the first semester.
Keywords: Adult learner; general equivalency diploma; post-secondary; transition.